Prytanée militaire et éducation patriotique au Gabon - Frederick Mba Missang (Éducation et Socialisation)
To what extent do the different teachings given at the Military school of Libreville reinforce a patriotic education? We attempt at answering this question through an analysis based on several resources from this institution going from a qualitative survey to the historiography of the nation. From a comprehensive approach, the objective of this article is to demonstrate that in a Gabonese context marked by a crisis on patriotic values due to the dysfunction of public schools since 1990, the Military school with its inspired rigorous teaching methods, is an important actor at the service of the whole nation, in terms of socialization and the national defense. It is a school that definitely participates to build the nation.